Hubungan Pengetahuan Orangtua Tentang Pendidikan Seks dengan Perilaku Pencegahan Kekerasan Seksual Anak Usia Prasekolah - Ridwan, Ridwan; Wijaya, Intan Prastihastari; Lestariningrum, Anik; ‘Aisy, Ratih Rahadatul (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This research aims to determine the relationship between parental knowledge about sex education and sexual violence prevention behavior in pre-school children at RA Siti Chotidjah Grogol, Kediri Regency. Researchers used quantitative methods with the Kendall Tau correlation test. The results of the research also show a significant relationship between parental knowledge and the prevention of sexual violence with a result of 0.012 < 0.05, with a positive correlation direction of 0.271 which has a fairly appropriate correlation as stated in the maximum correlation value, meaning there is a relationship between parental knowledge about sex education. in preventing sexual violence in pre-school children